2001
DOI: 10.1034/j.1600-0420.2001.079002116.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of glaucoma on the quality of life of patients in Norway

Abstract: ABSTRACT.Purpose: To evaluate the feelings and experiences of patients living with glaucoma. Methods: A questionnaire was delivered to patients willing to take part, at a regular visit to their ophthalmologist, for filling in anonymously at home. A total of 589 questionnaires were returned. Results: More than 80% reported negative emotions on learning that they had glaucoma, one-third were afraid of going blind. Half the patients had no visual problem at all, 14% complained of poor or very poor vision. This pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(85 citation statements)
references
References 12 publications
5
76
0
2
Order By: Relevance
“…7 Over the years, several glaucoma-specific patient-reported outcome (PRO) instruments have been developed. [3][4][5][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] While these instruments measure various QOL domains such as activity limitation, symptoms, convenience of eye-drop use, treatment of side effects and satisfaction; each instrument typically measures only one domain. 7,24 For instance, the Glaucoma Quality of Life (GQL-15) measures only activity limitation, 3,25 the Treatment Satisfaction Survey of Intra-ocular Pressure (TSS-IOP) was developed to assess treatment satisfaction and side effects of glaucoma medication, 13 and the Comparison of Ophthalmic Medication for Tolerability (COMTOL) measures tolerability and compliance of glaucoma eyedrops.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Over the years, several glaucoma-specific patient-reported outcome (PRO) instruments have been developed. [3][4][5][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] While these instruments measure various QOL domains such as activity limitation, symptoms, convenience of eye-drop use, treatment of side effects and satisfaction; each instrument typically measures only one domain. 7,24 For instance, the Glaucoma Quality of Life (GQL-15) measures only activity limitation, 3,25 the Treatment Satisfaction Survey of Intra-ocular Pressure (TSS-IOP) was developed to assess treatment satisfaction and side effects of glaucoma medication, 13 and the Comparison of Ophthalmic Medication for Tolerability (COMTOL) measures tolerability and compliance of glaucoma eyedrops.…”
Section: Introductionmentioning
confidence: 99%
“…2 As a result, glaucoma can have a significant impact on issues such as, emotional well-being, social relationships, and financial constraints. [3][4][5][6] Therefore, traditional clinical measures of glaucoma (intraocular pressure, optic nerve head evaluation and visual field examination) fail to elicit the actual impact of glaucoma on a patient's quality of life (QOL). 7 Over the years, several glaucoma-specific patient-reported outcome (PRO) instruments have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…(Curtis et al, 2008) A Norwegian study found that despite patient satisfaction with instructions and education, patients' knowledge about glaucoma was weak, and 20% missed information. (Odberg et al, 2001) Hahn has identified 3 patient-centered strategies for helping physicians detect and address patient adherence to glaucoma medication, recognizing that patients naturally want their physicians to see them as good patients. (Hahn, 2009) The first strategy is a 4-step adherence assessment interview that redefines the good patient as someone who works collaboratively with their physician to overcome the normal barriers to adherence, rather than as someone who adheres to treatment.…”
Section: Methods For Improving Adherencementioning
confidence: 99%
“…(Blondeau et al, 2007) Knowledge about side effects and the importance of adherence is lacking in many patients, regardless of health literacy. (Odberg et al, 2001) Hyperemia is one of the side effects of prostaglandins that can significantly reduce adherence and persistence. A multicenter, randomized patient education program on hyperemia associated with bimatoprost therapy was provided to 106 patients in an effort to encourage patients to continue using their medication in order to lower IOP.…”
Section: Methods For Improving Adherencementioning
confidence: 99%
See 1 more Smart Citation